Application of Management Principles in Production Orchestra Performance in Indonesia - Adha, Yasril; Rosa.P, Della; Surayya, Yade (Institut Seni Indonesia Padangpanjang, 2023)
The purpose of writing this article is to examine musical performances in the orchestral format in Indonesia, which were previously considered high culture, but currently, orchestral performances are of great interest to the public in different ways. This can be seen from the many requests from the Indonesian people to perform modern orchestral performances at various large and prestigious events. Modern orchestral performances generally occur within the context of the performing arts industry. Because in the context of the Indonesian orchestra management industry, it cannot be separated from managing adequate and solid performance production through good management. Managing Indonesian orchestra performances today requires the application of effective management principles. This research uses a management analysis framework in the management of orchestra performances by Harold Koontz and Cyril O'Donnell in their book Principles of Management: An Analysis of Management Functions by taking a performing arts management approach.